Professional consensus on orthodontic risks: what orthodontists should tell their patients. A cross-sectional study at Saidu college of dentistry, Swat - Erum Behroz Khan; Huda Ghaffar; Neelam Shah Jehan; Muhammad Zaheen; Tufail Muhammad; Ali Raza Jafri (Journal of the Pakistan Medical Association, 2025)
The importance of transparent communication regarding orthodontic risks during the informed consent process in paramount in terms of ensuring a strong orthodontist-patient relationship. Conducted on a national scale in Pakistan, the current study was planned to establish a consensus among orthodontic professionals regarding critical risks involved in such a discussion. The cross-sectional survey involving 132 orthodontists across Pakistan led to the emergence of 10 key risks, including relapse, treatment duration and gingivitis. However, the study’s sole focus on orthodontists’ perspectives limited its insights, overlooking invaluable input from patients’ experiences. Nevertheless, the consensus underscored the significance of addressing these risks to ensure informed consent and patient autonomy. Going forward, it is imperative to customise this evidence-based information according to individual patient needs, and maintain an ongoing dialogue regarding potential risks, fostering a collaborative approach to orthodontic care and decision-making. Key Words: Orthodontic risks communication, Patient education and safety, Medico-legal complications, Informed consent.